Customs Regulations and Risk Management and Town Planning Marketing on the Way to Smart Cities in the Global Economy - Arynova, Zh.; Ashirbaeva, A.; Ustik, T.; Larka, L.; Chernysh, T.; Volkova, O. (Economic Affairs, 2024)
In a rapidly changing and technologically developed world, the adaptation of customs provisions in the direction of smart cities is becoming more and more relevant. European cities are leading the way in implementing innovations that are transforming traditional approaches to customs management and town marketing. The purpose of the article is to analyze the smartization strategies of cities in Europe, focusing on the integration of customs directives and risk management in this process by studying their impact on the global economy. The article provides a detailed overview of official reports on the processes of intellectualization of modern cities, reveals current trends and the development of the latest technologies used in European smart cities. The results show that the effective management of customs standards significantly contributes to the optimization of city operations, increasing transparency and attracting investment. The importance of such an approach is reinforced by the analysis of town planning marketing, which includes the creation of a city brand and the promotion of innovative projects. The conclusions of the work indicate the need for further research in this area and the development of comprehensive strategies that would take into account both the technological and socio-economic aspects of the smartization of cities through the strengthening of urban infrastructure. The resulting data can serve as a basis for the formation of effective development policies and strategies that can accelerate the integration of cities into the global economy, contributing to the creation of sustainable and innovative urban environments through customs procedures and the management of challenges to legislation.
Keywords: Customs rules; customs risks; town planning marketing; global economy; smartization of cities; international trade; electronic management